Mapping the proteome landscape of Indian Zebu (Sahiwal) spermatozoa using high-resolution mass spectrometry and in-silico annotation - Vanya Bhushan; Syed Azmal Ali; Abhishek Parashar; Sudarshan Kumar; Ashok Kumar Mohanty (Animal Biotechnology, 2024)
Proteomic analysis of sperm cells offers significant insights into proteins’ structural, functional, and localization aspects within biological systems. Sahiwal, a native Indian cattle breed, is well known for its disease resistance, calving ease, and resilience to drought. This study addressed the gap in Sahiwal’s comprehensive sperm proteome profiling data. The research involved the global in-silico quantitative high-resolution mass spectrometry-based protein profiling of Indian Zebu sperm, identifying 4651 sperm proteins. Beyond mere identification, the study characterized these proteins at a sub-organellar level to facilitate a better understanding of their functional attributes. Gene Ontology analysis of sperm proteins facilitated the segregation of proteins based on their function, localization, and mode of action. The study revealed that despite the limited number of organelles, sperm cells encapsulate a wide array of crucial proteins, compensating for the deficiency of organelles through the presence of multifunctional proteins. Most identified sperm proteins actively participate in spermatogenesis, motility, acrosome reaction, capacitation, and seminal plasma binding, directly or indirectly. Notably, the results not only present the highest number of identified bovine sperm proteins but also hold the potential to pave the way for empirical research on sperm functionality, egg-sperm interaction, sperm-sex sorting biomarkers, sperm quality, and bull fertility.